Analysis of misconceptions of senior high school students on biodiversity materials, interactions, and their role in nature - Mohammad Liwa Ilhamdi; Aulia Vina Rahmani; Muhamad Syazali (Jurnal Pijar Mipa, 2022)
Forming the student's right and correct concept in Biology science is necessary. Lack of understanding of concepts in students can lead to a discrepancy of concepts called misconceptions. This study aims to identify the profile of students' misconceptions in grade tenth on material biodiversity, interactions, and their roles in nature. The results showed that the average conception of students was more significant than those who experienced misconceptions. The average concept is 50.00%, while the average who experiences misconceptions is 29.41%, and 20.59% of students do not answer. If it is categorized in the assessment category, the percentage of misconceptions is in low category.